A pilot clinical trial to objectively assess the efficacy of electroacupuncture on gait in patients with parkinson's disease using body worn sensors - Lei, Hong; Schwenk, Michael (PLOS ONE, 2016)
BACKGROUND: Gait disorder, a key contributor to fall and poor quality of life, represents a major therapeutic challenge in Parkinson's disease (PD). The efficacy of acupuncture for PD remains unclear, largely due to methodological flaws and lack of studies using objective outcome measures.
Gesehen am 14.08.2017